HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL TIKTOK DENGAN FENOMENA FEAR OF MISSING OUT (FOMO) PADA REMAJA DI SMAN 1 INDRALAYA UTARA - Emy Husnita; Alrefi (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
The phenomenon of Fear of Missing Out (FOMO) is one of the psychological impacts frequently experienced by adolescents in the digital era, along with the increasing use of social media such as TikTok. This study aims to examine the relationship between the intensity of TikTok use and FOMO among eleventh-grade students at SMA Negeri 1 Indralaya Utara. The research employed a quantitative correlational approach with purposive sampling technique. The research instrument was tested for validity and reliability, and all items were found to be valid and reliable (α > 0.70). Normality testing indicated that the data were not normally distributed (p < 0.05), so the analysis was conducted using Spearman’s rho correlation test. The results showed a significant positive relationship between TikTok usage intensity and FOMO (rs = 0.590; p = 0.000). This means that the higher the students’ intensity in using TikTok, the higher their level of FOMO. These findings highlight the importance of digital literacy education and guidance from both parents and schools to ensure that adolescents can use social media wisely without causing psychological pressure.